2012
DOI: 10.1002/mrc.3892
|View full text |Cite
|
Sign up to set email alerts
|

WYE‐120318, a ring contraction product of methylnaltrexone, and structure revision of coniothyrione

Abstract: A contracted ring degradation product, WYE-120318 (compound 2), was discovered during the development phase for methylnaltrexone bromide (compound 1) drug substance. The compound was isolated by high-performance liquid chromatography fractionation, and its structure was determined by spectroscopic data analyses. WYE-120318 is formed from methylnaltrexone through a benzyl-benzilic acid type rearrangement reaction to yield an α-hydroxy-cyclopentanecarboxylic acid substructure. The proposed structure and the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 16 publications
(28 reference statements)
0
16
0
Order By: Relevance
“…44 The structure was determined using a combination of HSQC/HMBC data to locate the chloro substituent at the 3-position as shown by 12 based on the absence of a correlation from the methine singlet to the C1 carbonyl. More recently in a study by Kong et al, 45 based on empirical carbon chemical shift arguments, it was proposed that the location of the chloro substituent should be at the 4-position as shown by 13 rather than the 3-position as originally reported. That study was reported without the acquisition of any new NMR data.…”
mentioning
confidence: 89%
“…44 The structure was determined using a combination of HSQC/HMBC data to locate the chloro substituent at the 3-position as shown by 12 based on the absence of a correlation from the methine singlet to the C1 carbonyl. More recently in a study by Kong et al, 45 based on empirical carbon chemical shift arguments, it was proposed that the location of the chloro substituent should be at the 4-position as shown by 13 rather than the 3-position as originally reported. That study was reported without the acquisition of any new NMR data.…”
mentioning
confidence: 89%
“…Cyclopentachromones (CPCs), the tricyclic cyclopentabenzopyan-9-one derivatives, are relatively rare in nature. Only a few in this family has so far been reported from fungi, including coniochaetones A–D [ 1 , 2 , 3 ] and E–I [ 4 ], coniothyrione [ 5 , 6 ], diaportheones A–B [ 7 ], preussochromones D–F [ 8 ], cryptosporioptide [ 9 ], and remisporine A [ 10 ]. Remisporine B is a unique CPC dimer resulting from a spontaneous Diels-Alder reaction of remisporine A [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a revision of the chloro substitution in the structure of coniothyrione based on the analysis of previously published data was reported (Fig. ) . The reported investigation and interpretation piqued our interest and led us to rigorously explore the basis of this new structure proposal.…”
Section: Introductionmentioning
confidence: 99%
“…The original structure, 1 , was chosen on the basis of the absence of what was believed to be a key 3 J CH HMBC correlation from the proton assigned as H4 to C1 . As pointed out in the work of Kong et al ., the bond angle between these two atoms is ~70°. This dihedral angle suggests that the 3 J CH coupling would be expected to be small on the basis of a Karplus‐like angular dependence on the coupling constant thus leaving the utility of this negative evidence questionable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation